ANALYSIS OF FACTORS AFFECTING NURSE ANXIETY DURING PANDEMIC COVID-19 - Indri Lestari; Nursalam Nursalam; Aria Aulia Nastiti (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2021)
Introduction: The development of cases of Corona Virus Disease 2019 (Covid-19) in Pati Regency which is increasing every day causes anxiety in nurses. The purpose of the study was to analyze the factors that influence the anxiety level of nurses during the Covid-19 pandemic.Method: The research design used was descriptive analytic with a cross-sectional approach. The sample size was 55 respondents, taken according to the inclusion criteria and sampling using the proportional stratified random sampling technique. The inclusion criteria in this study were nurses who worked in room units that did not treat Covid-19 patients and were cooperative at RSUD Kayen Pati. The independent variables in this study were perceptions of risk, workload as well as information and training. The dependent variable in this study was the level of anxiety of nurses. The instrument used for the perception of risk as well as information and training was a questionnaire from Gershon et al (1995), for the workload instrument using a questionnaire fromÂ  Nursalam (2016) while for anxiety instruments using a Depression Anxiety Stress Scale (DASS) 42 questionnaire. Analysis using a test Logistics Regression statistic with significance level p<0.05.Results: The results showed that there was an influence between information and training (0.000), workload (0.000) and perceptions of risk (0.001) with nurses' anxiety levels during the Covid-19 pandemic. The most dominant factor giving the relationship between nurses' anxiety levels during the Covid-19 pandemic was information and training.Conclusion: Information and training factors, workload and perceptions of risk have an influence on nurses' anxiety levels during the Covid-19 pandemic.